Brothers in Arms: The Value of Coalitions in Sanctions Regimes - Sonali Chowdhry; Julian Hinz; Katrin Kamin; Joschka Wanner (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines the impact of coalitions on the economic costs of the 2012 Iran and 2014 Russia sanctions. By estimating and simulating a quantitative general equilibrium trade model under different coalition setups, we (i) dissect welfare losses for sanctions senders and target; (ii) compare prospective coalition partners; (iii) investigate "optimal" coalitions that maximise payoff from sanctions; (iv) provide bounds for sanctions potential, i.e. the maximum welfare change attainable when sanctions are scaled vertically up to an embargo, and horizontally up to a global regime. Relative to unilateral action, we find that coalitions magnify welfare losses imposed while their impact on domestic welfare loss incurred depends on the design and sectoral dimension of sanctions. Hypothetical cooperation of large developing economies such as China additionally raises the deterrent force of coalitions. Additionally, we quantify transfers that equalise welfare losses across coalition members to further demonstrate asymmetries in the relative economic burden of sanctions. In all scenarios, we implement a novel Bayesian bootstrap procedure that generates confidence bands for simulation outcomes.
Keywords: F13; F14; F17; F51; 330; sanctions; embargoes; alliances; sectoral linkages